Sub-20-nm magnetite-based core-shell nanoparticles with strong magnetic, magnetoelectric, and nanocatalytic properties; Ceramics International; Vol. 51, iss. 16, Pt. 1 - Urakova A. O. Alina Olegovna; Baksheev A. I. Artem Igorevich; Pryadko A. Artyom; Grubova I. Yu. Irina Yurievna; Surmeneva M. A. Maria Alexandrovna; Chernozem P. V. Polina Viktorovna; Mukhortova Yu. R. Yulia Ruslanovna; Vagner D. V. Dmitry Viktorovich; Gerasimov E. Yu. Evgeny; Kazantsev S. Sergey; Lozhkomoev A. S. Aleksandr Sergeevich; Lisitsyn S. Sergey; et al. (2025, 2025)
Title screen